Timing of menarche in Norwegian girls: associations with body mass index, waist circumference and skinfold thickness - Heiko Bratke; Ingvild Særvold Bruserud; Bente Brannsether; Jörg Aßmus; Robert Bjerknes; Mathieu Roelants; Pétur B. Júlíusson (BMC, 2017)
Abstract Background Research studies show conflicting results regarding the association between menarche and body weight. The purpose of the present study was to investigate if anthropometric indicators of body composition, body mass index (BMI), waist circumference (WC), triceps (TSF) and subscapular skinfold (SSF) thicknesses, were differentially associated with age at menarche in Norwegian girls. Methods The association between menarche and BMI, WC, TSF and SSF was investigated in 1481 girls aged 8-15.5 years, and in a subgroup of 181 girls with menarche during the 12 months prior to examination. Anthropometric measures were categorized as low (< −1SDS), average (−1 ≤ SDS ≤ +1) or high (> 1SDS), and menarche according to this classification was analysed with Kaplan-Meier curves and unadjusted and adjusted Cox regression. Results The median age at menarche in the total sample was 13.1 years. In the unadjusted models, low categories of all traits were associated with later menarche, and high categories with earlier menarche. When adjusted for other covariates, earlier menarche was only related with a high BMI (Hazard Ratio 1.41, 95% confidence interval (CI) 1.07, 1.85), and later menarche with a low BMI (HR 0.53, 95%CI 0.38, 0.75) and low SSF (HR 0.54, 95%CI 0.39, 0.75). In girls with recent menarche, early menarche was significantly associated with a high BMI in the final model (HR 1.79, 95%CI 1.23, 2.62). Conclusions The timing of menarche was associated with the BMI, WC, TSF and SSF, but more strongly so with the BMI. These associations may be related to a common tempo of growth, as the mean age at menarche has remained stable during the last decades during a time period while the prevalence of overweight and obesity has increased significantly.